PEMBINAAN KESEHATAN REMAJA DENGAN AKHLAK DAN BERBUDAYA SEHAT - Farida Ariyani; Yulia Arifin (LPPM STIKes MERCUBAKTIJAYA Padang, 2021)
Background: Adolescents are an age group who experience emotional and behavioral instability. These adolescents need a place and media to get information and knowledge about their growth and development as well as solutions to reproductive problems and their behavior. This community service aims to provide a forum for teenagers to develop their potential and have positive activities in filling their spare time. Method: The mechanism for the implementation of this activity is carried out by adopting action research steps consisting of planning, acting, observing and evaluating, reflecting Result: The forum or media used by teenagers for spiritual activities is teenage wirid. Wirid help adolescents to increase their understanding of religion and worship. In addition, in Palembayan already built of Laga-laga. They can do alo-ambek and tambua martial arts for the development of regional arts and culture. Palembayan youth groups to also have social media groups to share knowledge and information about adolescent health and activities that will be carried out for these adolescents.